Acacetin 7-O-α-l-rhamnopyranosyl (1–2) β-D-xylopyranoside Elicits Life-span Extension and Stress Resistance in Caenorhabditis elegans. (3rd October 2015) - Asthana, Jyotsna; Yadav, Deepti; Pant, Aakanksha; Yadav, A. K.; Gupta, M. M.; Pandey, Rakesh
Abstract: The advancements in the field of gerontology have unraveled the signaling pathways that regulate life span, suggesting that it might be feasible to modulate aging. To this end, we isolated a novel phytomolecule Acacetin 7-O-α- l -rhamnopyranosyl (1–2) β-D-xylopyranoside (ARX) from Premna integrifolia and evaluated its antiaging effects in Caenorhabditis elegans . The spectral data analysis revealed the occurrence of a new compound ARX. Out of the three tested pharmacological doses of ARX, viz. 5, 25, and 50 µM, the 25-µM dose was able to extend life span in C. elegans by more than 39%. The present study suggests that ARX affects bacterial metabolism, which in turn leads to dietary restriction (DR)-like effects in the worms. The effect of ARX on worms with mutations ( mev-1, eat-2, sir-2.1, skn-1, daf-16, and hsf-1 ) indicates that ARX-mediated life-span extension involves mechanisms associated with DR and maintenance of cellular redox homeostasis. This study is the first time report on longevity-promoting activity of ARX in C. elegans mediated by stress and DR-regulating genes. This novel phytomolecule can contribute in designing therapeutics for managing aging and age-related diseases.